Proteins that contain a functional Z-DNA-binding domain localize to cytoplasmic stress granules - Ng, Siew Kit; Weissbach, Rebekka; Ronson, George E.; Scadden, A. D. J. (Oxford University Press (OUP), 2013)
Long double-stranded RNA may undergo hyper-editing by adenosine deaminases that act on RNA (ADARs), where up to 50% of adenosine residues may be converted to inosine. However, although numerous RNAs may undergo hyper-editing, the role for inosine-containing hyper-edited double-stranded RNA in cells is poorly understood. Nevertheless, editing plays a critical role in mammalian cells, as highlighted by the analysis of ADAR-null mutants. In particular, the long form of ADAR1 (ADAR1(p150)) is essential for viability. Moreover, a number of studies have implicated ADAR1(p150) in various stress pathways. We have previously shown that ADAR1(p150) localized to cytoplasmic stress granules in HeLa cells following either oxidative or interferon-induced stress. Here, we show that the Z-DNA-binding domain (Zα(ADAR1)) exclusively found in ADAR1(p150) is required for its localization to stress granules. Moreover, we show that fusion of Zα(ADAR1) to either green fluorescent protein (GFP) or polypyrimidine binding protein 4 (PTB4) also results in their localization to stress granules. We additionally show that the Zα domain from other Z-DNA-binding proteins (ZBP1, E3L) is likewise sufficient for localization to stress granules. Finally, we show that Z-RNA or Z-DNA binding is important for stress granule localization. We have thus identified a novel role for Z-DNA-binding domains in mammalian cells.